2021
DOI: 10.3390/en14206783
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Efficiency of a Batch Boiler and Emissions of Harmful Substances during Combustion of Various Types of Wood

Abstract: In the paper, the authors focused on the environmental problems of pollution emissions caused by households using batch boilers fired with solid fuels. The aim of this study is to analyse the course of changes in the actual efficiency and emission of a solid fuel updraft boiler, the most popular type of batch boilers used in Poland in recent years. The subject of analysis is the comparison of the values of atmospheric emissions of harmful substances depending on the type of wood burnt in the boiler. The invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…For those sites, the thermal loads require hot water of 90°C, which was recognised as the most efficient heat source with a thermal efficiency of 95%. The previous studies indicated that the efficiency of the most steam efficient boilers is below 78% (Pelka et al ., 2021). All thermal loads at the dairy plant were therefore analysed by the energy team to determine their suitability for deferral to hot water.…”
Section: Resultsmentioning
confidence: 99%
“…For those sites, the thermal loads require hot water of 90°C, which was recognised as the most efficient heat source with a thermal efficiency of 95%. The previous studies indicated that the efficiency of the most steam efficient boilers is below 78% (Pelka et al ., 2021). All thermal loads at the dairy plant were therefore analysed by the energy team to determine their suitability for deferral to hot water.…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that fuels with a higher volatile content ignited faster and burnt more intensely, probably due to their lower density. The net calorific value of each fuel was also analyzed and determined to be approximately 16 MJ/kg [1].…”
Section: A Short Review Of the Contributions In This Special Issuementioning
confidence: 99%
“…This Special Issue of Energies contains successful submissions [1][2][3][4][5][6] relating to the subject area of "Energy Production from Biomass Valorization". The composition of residual biomass, its low cost, and its abundance make it a realistic option for the production of the energy required for the sustainable development of human society [7].…”
mentioning
confidence: 99%
“…Flue gas recirculation is a primary method of nitrogen oxide reduction and is realized by returning some of the flue gas and reintroducing it to the flame area (the reduction in the emissions, particularly NO x , is commonplace; it is widely applied in the industry [28,32,33] and is analyzed both technically [34][35][36] and in its technological aspect [37,38]). In energy systems, this solution is referred to as FGR.…”
Section: Introductionmentioning
confidence: 99%